Comparative Analysis of Carbetocin and Oxytocin in the Prevention of Postpartum Hemorrhage following Caesarean Section - Desai, Dr. Dhruv; Chaudhary, Dr. Ruta; Pawar, Dr. Atul (International Journal of Innovative Research in Medical Science, 2025)
Introduction: Postpartum haemorrhage (PPH) remains a leading cause of maternal morbidity and mortality, particularly in caesarean deliveries. Oxytocin is widely used but limited by its short half-life and instability. Carbetocin, a long-acting analogue, offers sustained uterotonic effect and may reduce the need for repeated dosing. This study compared the efficacy of carbetocin versus oxytocin in preventing PPH during caesarean section. Method: A randomized comparative study was conducted at Holy Family Hospital, New Delhi, from February 2023 to January 2024. A total of 144 full-term women undergoing elective or emergency caesarean section were randomly allocated into two groups: Group A received carbetocin 100 μg IV, and Group B received oxytocin 20 IU IV infusion. Primary outcomes included intraoperative and postoperative blood loss, haemoglobin drop, and need for additional uterotonics. Secondary outcomes included surgical interventions, transfusion, maternal morbidity, neonatal outcomes, and side effects. Result: Group A had significantly lower mean blood loss (527.2 ± 58.1 ml vs 598.9 ± 138.4 ml; p=0.0001), smaller haemoglobin drop (0.62 ± 0.49 g/dl vs 0.91 ± 0.74 g/dl; p=0.019), and reduced need for additional uterotonics (15.3% vs 66.7%; p<0.0001). Neonatal Apgar scores were higher in Group A, while complications and maternal side effects were comparable. Conclusion: Carbetocin is more effective than oxytocin in reducing blood loss and need for additional uterotonics during caesarean section, with comparable safety.